New insights into the mechanisms of high‐fat diet mediated gut microbiota in chronic diseases. Issue 1 (5th January 2023) - Chen, Jiali; Xiao, Yuhang; Li, Dongmei; Zhang, Shiqing; Wu, Yingzi; Zhang, Qing; Bai, Weibin
Abstract: High‐fat diet (HFD) has been recognized as a primary factor in the risk of chronic disease. Obesity, diabetes, gastrointestinal diseases, neurodegenerative diseases, and cardiovascular diseases have long been known as chronic diseases with high worldwide incidence. In this review, the influences of gut microbiota and their corresponding bacterial metabolites on the mechanisms of HFD‐induced chronic diseases are systematically summarized. Gut microbiota imbalance is also known to increase susceptibility to diseases. Several studies have proven that HFD has a negative impact on gut microbiota, also exacerbating the course of many chronic diseases through increased populations of Erysipelotrichaceae, facultative anaerobic bacteria, and opportunistic pathogens. Since bile acids, lipopolysaccharide, short‐chain fatty acids, and trimethylamine N ‐oxide have long been known as common features of bacterial metabolites, we will explore the possibility of synergistic mechanisms among those metabolites and gut microbiota in the context of HFD‐induced chronic diseases. Recent literature concerning the mechanistic actions of HFD‐mediated gut microbiota have been collected from PubMed, Google Scholar, and Scopus. The aim of this review is to provide new insights into those mechanisms and to point out the potential biomarkers of HFD‐mediated gut microbiota. Abstract : Gut microbiota dysbiosis increases the host's susceptibility to diseases. Identified characteristic microbes in high‐fat diet (HFD) induced obesity, diabetes, gastrointestinal diseases, neurodegeneration, and cardiovascular diseases. Bile acids, lipopolysaccharide, short‐chain fatty acids, and trimethylamine N‐oxide are the commonalities in HFD‐induced chronic diseases. FXR, TGR5, NF‐κB, PPAR‐γ, and PERK signaling were critical for the interacted mechanisms toward microbiota modulation. Provided new insights into mechanisms among microbiota, metabolites, and immune responses in chronic diseases. Highlights: Gut microbiota dysbiosis increases the host's susceptibility to diseases. Identified characteristic microbes in high‐fat diet (HFD) induced obesity, diabetes, gastrointestinal diseases, neurodegeneration, and cardiovascular diseases. Bile acids, lipopolysaccharide, short‐chain fatty acids, and trimethylamine N ‐oxide are the commonalities in HFD‐induced chronic diseases. FXR, TGR5, NF‐κB, PPAR‐ γ, and PERK signaling were critical for the interacted mechanisms toward microbiota modulation. Provided new insights into mechanisms among microbiota, metabolites, and immune responses in chronic diseases.